Epidemic of Isothiazolinone Allergy in North America: Prevalence Data From the North American Contact Dermatitis Group, 2013–2014. Issue 3 (May 2017) - Zirwas, Matthew J.; Hamann, Dathan; Warshaw, Erin M.; Maibach, Howard I.; Taylor, James S.; Sasseville, Denis; DeKoven, Joel G.; Fransway, Anthony F.; Mathias, C.G. Toby; Zug, Kathryn A.; DeLeo, Vincent A.; Fowler, Joseph F.; et al.
Abstract : Background: Preservative sensitivity patterns evolve with changing use patterns in products. During the last decade, the use of methylisothiazolinone (MI) at higher concentrations in both leave-on and rinse-off products has significantly increased. This is the first North American Contact Dermatitis Group reporting cycle that includes both methylchloroisothiazolinone (MCI)/MI and MI data. Objective: The aim of this study was to report the prevalence of isothiazolinone allergy (MCI/MI and MI) in the North American Contact Dermatitis Group patch-test population from January 1, 2013, to December 31, 2014. Methods: At 13 centers in North America, 4860 patients were patch tested in a standardized manner with a series of 70 allergens, including MCI/MI 0.01% aqueous (aq) and MI 0.2% aq. Results: Three hundred five patients (6.3%) had a positive reaction to MCI/MI; this is a significant increase from the previous cycle (5.0%, 2011–2012; P = 0.011). Five hundred twenty-one patients (10.7%) had a positive reaction to MI. These 2 isothiazolinones were among the most common preservative allergens in the 2013 to 2014 cycle; 11.9% of patch-tested individuals were allergic to 1 or both isothiazolinones. Individuals with MCI/MI and MI allergy were significantly more likely to have occupationally related skin disease ( P < 0.0001) and hand dermatitis ( P < 0.0001, P = 0.0474). Conclusions: The epidemic of isothiazolinone sensitivity documented in Europe is now in North America. Patch testing with only MCI/MI 0.01% aq will miss approximately half of isothiazolinone allergy cases, whereas testing with only MI 0.2% aq will miss approximately 10% of isothiazolinone allergy cases.